Algerian Working Women's Position between Social Dynamics and Culture: a Case Study of Married Female Breadwinners - BOUGUESRI, Imene (l’Université de Mostaganem, 2022)
A rising interest is nowadays on the self-reliant individual who assists her/himself without having to rely on the help of others. Many women have adopted this ideology pursuing a career and an independent lifestyle but found themselves dragged by similar policing forces to those of the system they sought to rebel against. Their present condition is actually the result of an alliance between two major forces patriarchy and market economy (what is later referred to in this work as neopatriarchy) that function in such a way as to reproduce strategies that offer seemingly empowering opportunities that later systematically contribute to disciplining and confining women into pre-established molds of femininity. The present investigation is built around an underlying assumption that the empowerment game women have been involved in is bound by the same old rules that once governed their relationships as an oppressed category. Since women represent one of the most heterogeneous social categories; it is, therefore, one of the most controversial and problematic in research. We have narrowed down the scope of analysis to the educated female, who could earn a position in the job market which is considered a success in the contemporary economically-oriented environment and who happens to be a breadwinner in her household. It seeks to evaluate the degree of empowerment she has reached particularly through the power interplay within the family, and whether her status as breadwinner is part of the empowerment process. The research work at hand consists of four chapters; Chapter one provides a close insight into the feminist literature on the most controversial issues relating to the dichotomized and essentialized gender relations. Chapter two attempts to contextualize the debate over the female condition in Algeria and unravel the systematic reconstruction of femininity in accordance with the dictates of the socioeconomic environment that utilizes strategies of governmentality to ensure the embodiment of normative conduct among women. Chapter three is divided into two phases, the first one seeks to analyze working women’s self-identification and realization through choice, and whether their actual situation is empowering and liberating or the realization of the new sexual contract (as an amalgam of patriarchy and the market economy). The second one teases out the impact of gender, status, and income on power relations within marriage. Chapter four is informed with a need to frame an inclusive project of gender justice that redefines the relation of knowledge production to the actual application of policies and their implementation within the larger civil institutions to achieve tangible results and popularize gender awareness among community members.